SPRITUALITAS YESUS - Nur Fitriyana (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2017)
Jesus has spiritual revolution but he is not a political revolutionist. He did not try to reform the ruler in his time. The revolution in the sense of Jesus was to lift up the God values in this time. It is called as the social revolution. The revolution means the social repentance in the context of social relation. Jesus as the man of weak Jewish society in the time hoped to get the freedom of the Rome tyranny. Jesus was chosen as the social and spiritual revolutionist as the mission from God as the mission that was love Allah in the deepest heart and soul, love the people and the selves.